The Effect of Teaching Teacher Competence on Student Learning Evektivity in Mts Tebing Syahbandar District - Nova Erawati Sidabalok (PT Inovasi Pratama Internasional, 2022)
This study discusses the influence of teacher competence in teaching in the classroom on the effectiveness of student learning at Mts Al Muslimin Hamlet IV Paya Pasir Village. Syahbandar Cliff District . Formulation of the problem in this research These are: How is the implementation of teaching teacher competence in class on the effectiveness of student learning at MTs Al Muslimin Hamlet IV Paya Pasir Village, Tebing Syahbandar District, Is there an influence of teacher teaching competence in class on student learning effectiveness at MTs Al Muslimin Hamlet IV Paya Pasir Village, Tebing Syahbandar District. From the results of the study, there is an influence of teacher competence in class on the effectiveness of student learning at MTs Al Muslimin Hamlet IV Paya Pasir Village, Tebing Syahbandar District. Judging from the results of the calculations that the researchers have done, the influence of teacher competence in class on the effectiveness of student learning at MTs Al Muslimin Hamlet IV Paya Pasir Village, Tebing Syahbandar District, is so great. Because of the importance of the influence of teacher competence on the effectiveness of student learning here the teacher must be able to develop his competence. that is, with the result of the contribution effect of 0.753 or 75.3% of the Y variable.